MNE responses to carbon pricing regulations: Theory and evidence - Nippa, Michael; Patnaik, Sanjay; Taussig, Markus (Journal of International Business Studies, 2021)
Abstract This paper develops theory suggesting that, relative to purely domestic firms, multinational enterprises (MNE) have greater incentives and strategic and operational means to respond to expanding carbon emissions constraints. We test our resulting hypotheses with data on changes in carbon emissions by over 6,000 industrial plants during Phase 2 (2008–2012) of the European Union’s Emissions Trading Scheme. We find that MNE maintain: (1) consistent carbon reductions across institutional contexts, and (2) an overall carbon performance edge over domestic firms. The carbon performance gap between MNEs and domestic firms narrowed, however, in host countries transitioning towards more stringent market regulatory systems. By demonstrating that the effects of national and international carbon regulations on firm behavior interact in important ways with each other and with firm characteristics, this paper deepens understanding of how institutions are likely to shape the ongoing energy transition towards a low-carbon economy.